Blogs as a pedagogical alternative to language teaching and learning / Alice Shanthi Kasawi @ Krisnan and Xavier Thayalan - Kasawi @ Krisnan, Alice Shanthi; Xavier Thayalan, . (2011)
This action research explores how a weblog project can be incorporated into an English language classroom. This project was aimed at motivating students to take advantage of authentic environments outside the classroom in order to practice language skills when they communicate with others through a non-face to face medium: weblogs. Therefore this study seeks to determine the benefits of using weblogs in the English language classrooms. The samples in the study were asked to reflect on their blogging experience and how it had aided them to improve their English language proficiency. Descriptive statistics shows that samples have a positive perception on blogs which can help them to learn English better. However further studies need to be conducted on matters related to how best blogs can be incorporated in the teaching and learning of English.